Suppression of BCG cell wall induced delayed-type hypersensitivity by BCG pre-treatment. I. Induction of adherent suppressor cells by live BCG injection and their characterization. - Kato, K (1981)
Previous injections of live Bacillus Calmette-Guérin (BCG) in mice produced a suppression of delayed-type hypersensitivity (DTH) induced by oil-treated BCG cell walls (CW). This phenomenon was analysed by the macrophage migration inhibition (MI) test in which peritoneal exudate cells (PEC) from live BCG-injected mice were mixed with PEC from BCG CW-immunized mice, with the result that the former cells suppressed the MI activity in the latter. We considered the Mi test to be a reliable method for demonstrating the existence of suppressor cells induced by the injection of live BCG. Moreover, we found that the adherent cells of PEC possessed a suppressive effect which was retained even after treatment with either anti-mouse Ig or anti-brain associated theta (BA theta) antigen; that the PEC from mice injected with live BCG on at least the 12th day before cell harvesting showed the suppression; and that the suppression operated across the H-2 barrier.